Direct Ruthenium Catalyzed C-C Coupling of Ethanol: Diene Hydro-Hydroxyethylation to Form All Carbon Quaternary Centers - Han, Hoon (2010)
[Image: see text] Under ruthenium catalyzed transfer hydrogenation conditions, direct C-C coupling of ethanol and 2-substituted dienes occurs to furnish products of hydro-hydroxyethylation: anti-configured neopentyl homoallylic alcohols. Identical adducts are generated from acetaldehyde under related conditions employing isopropanol as reductant.